Cognitive perceptions of second language acquisition in Chinese undergraduate ESL/EFL students: A mixed methods approach - Robert W. Elliott; Di Zhang (Institute of Advanced Engineering and Science, 2019)
With the continued demand for teachers of English as a Second Language (ESL/EFL) in China, colleges and universities in China continue to struggle with teaching oral English to high volumes of undergraduate students using faculty-centered strategies. This concurrent mixed-methods, single-level, case study intends to examine Chinese undergraduate students’ cognitive perceptions of their oral English ability as a segue to a more effective second language acquisition environment in a 21st Century global education. The data analysis revealed three main themes intersected by the findings of the quantitative and qualitative analyses. The findings from this and future studies are intended to guide leaders, administrators, scholars, and students to affect national and provincial policy, school and classroom-based practices, and personal strategies to enhance students’ ability to acquire their oral English skills.